Revisión bibliográfica de la hipomineralización del incisivo molar - Muñoz Rueda, Esteisy del Cisne (2021)
The objective of this study is to spread the knowledge of Molar incisor hypomineralization (IMH), as an emerging pathology, and to publicize the therapeutic options detected such as: non-invasive treatments and materials; which have greater effectiveness, in this case we have: remineralization, sealants and resin; The ART technique is the most used and fluorine varnish stood out among the materials. The (IMH) is a common dental development disorder produced by incomplete mineralization and maturation of enamel on the teeth which implies the presence of at least one permanent first molar, depending on the damage that can be produced during: prenatal, perinatal or postnatal period. It presents as multifactorial causes associated with systemic alterations or environmental aggressions which occurs after tooth eruption, characterized by localized loss of enamel, with cream-colored or yellowish-brown opacities and may be associated with the rapid progression of caries. A bibliographic documentary study was carried out establishing inclusion and exclusion criteria for each researched source, with the objective of formulate a bibliographic review that included 30 scientific articles in which the clinical characteristics, etiological factors, materials, and minimally invasive techniques were identified in the application of alternative treatments to treat IMH. According to the prevalence of IMH worldwide and especially; in Latin America its prevalence fluctuates between 12 to 33%; Thus, in Mexico we have a prevalence reported of 12.5% to 13.9%, in Chile 30.2%, Colombia 33.12%, in Peru 19.8% and in our country Ecuador, in the province of Manabí is detected mainly with 13.7%, and 20% in Quito, this shows that our country has an average rate in this type of dental syndrome. Key words: enamel, alteration, demineralization, opaciti